Assessment of in vitro Antioxidant Activities and Quantification of Total Phenolic and Flavonoid Contents in Extracts from The Thai Traditional Remedy “Ruean-Khi-Nok” and its Plant Constituents - Taingthum, Atchanika; Sakpakdeejaroen, Intouch; Panthong, Sumalee; Kanokkangsadal, Puritat (Asian Medical Journal and Alternative Medicine, 2024)
Introduction: Psoriasis is an immune-mediated inflammatory skin disease. The pathogenesis of psoriasis has been associated with an increase of oxidative stress. Therefore, natural antioxidant compounds (e.g., phenolics and flavonoids) might be beneficially used as an adjuvant. Ruean-Khi-Nok (RKN) remedy is a Thai traditional preparation used to treat psoriatic skin, consisting of nine plants in an equal proportion. Objectives: To investigate the antioxidant capability of the RKN remedy and its components using three chemical-based assays, as well as to determine phenolic and flavonoid contents. Methods: The 95% and 40% ethanolic extracts of RKN remedy and its plant components were investigated for in vitro antioxidant activities using DPPH and ABTS radical scavenging assay, as well as FRAP assay. The total phenolic and flavonoid contents in extracts were quantified using the Folin-Ciocalteu’s method and the aluminum chloride colorimetric method, respectively. Results: The results exhibited potential antioxidant activity of the 95% ethanolic extract of RNK remedy in the DPPH, ABTS and FRAP assay. In addition, it also contained high phenolic and flavonoid contents. Among individual plants, Piper wallichii extracts displayed outstanding antioxidant capability compared to the others. Conclusions: The RKN remedy is therefore highly promising antioxidant and might support the traditional use of RKN remedy for treatment of psoriatic skin. However, RKN should be investigated further for psoriasis treatment.